Purification and partial characterization of the capsular polymer of Haemophilus pleuropneumoniae serotype 5. - Inzana, T J (1987)
The capsular polymer (CP) of Haemophilus pleuropneumoniae serotype 5 was purified, and its chemical composition was analyzed. Radioimmunoassay experiments showed that the maximum amount of CP could be obtained from broth cultures of bacteria in the late stationary phase, rather than from bacteria washed off agar plates. The CP was precipitated from culture supernatant with 5 mM hexadecyltrimethylammonium bromide (Cetavlon) and solubilized with 0.4 M NaCl. Ninety percent of the CP in the culture supernatant was precipitated with Cetavlon, although some material remained insoluble after NaCl extraction. The CP was further purified by phenol extraction, ultracentrifugation, and Sepharose CL-4B gel filtration. The Kav of the CP from Sepharose CL-4B chromatography was 0.33. The CP preparation contained 85% hexosamine, 12% hexose, 3% phosphate, 0.17% protein, 0.20% nucleic acid, and 0.01% endotoxin. Thin-layer chromatography, an amino acid analyzer, and a glucose oxidase colorimetric kit were used to identify the sugar components of the hydrolyzed CP as glucosamine and glucose. Analysis of the native CP by 13C nuclear magnetic resonance indicated that amino, N-acetyl, and carboxyl groups were present and that the CP was a disaccharide.